2006
DOI: 10.4049/jimmunol.176.12.7288
|View full text |Cite
|
Sign up to set email alerts
|

IL-2 Is Required for the Activation of Memory CD8+ T Cells via Antigen Cross-Presentation

Abstract: Dendritic cells (DCs) are capable of capturing exogenous Ag for the generation of MHC class I/peptide complexes. For efficient activation of memory CD8+ T cells to occur via a cross-presentation pathway, DCs must receive helper signals from CD4+ T cells. Using an in vitro system that reflects physiologic recall memory responses, we have evaluated signals that influence helper-dependent cross-priming, while focusing on the source and cellular target of such effector molecules. Concerning the interaction between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
43
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 38 publications
7
43
0
Order By: Relevance
“…Either way, in the absence of CD4 + T cells, CD25 was poorly up-regulated on responding CD8 + T cells after VV, VSV, and LM infections. This is in line with previous studies that have demonstrated that CD4 + T cell help regulates CD25 expression on CD8 + T cells after HSV-1 infection (35) and DC vaccination (36) and correlated with the CD4 + T cell dependence of these responses. In contrast, previous studies reported no CD4 + T cell or CD25 involvement in the primary CD8 + T cell response to LCMV and LM infections (18,19,27,28), although other studies support a role for CD4 + T cells in primary CD8 + T cell responses to these and other immunogens (21,22).…”
Section: Cd40 Independent But Required Cd4supporting
confidence: 80%
“…Either way, in the absence of CD4 + T cells, CD25 was poorly up-regulated on responding CD8 + T cells after VV, VSV, and LM infections. This is in line with previous studies that have demonstrated that CD4 + T cell help regulates CD25 expression on CD8 + T cells after HSV-1 infection (35) and DC vaccination (36) and correlated with the CD4 + T cell dependence of these responses. In contrast, previous studies reported no CD4 + T cell or CD25 involvement in the primary CD8 + T cell response to LCMV and LM infections (18,19,27,28), although other studies support a role for CD4 + T cells in primary CD8 + T cell responses to these and other immunogens (21,22).…”
Section: Cd40 Independent But Required Cd4supporting
confidence: 80%
“…40 The strong cell proliferation might have been in part the result of an unspecific expansion of pre-activated CD8 + T cells in our cultures; help provided by MOG-specific CD4 + T cells might then boost the reactivity of those CD8 + T cells even further. 41 Although a thorough analysis of whether the proliferative response we observed was indeed due to expansion of in vitro-stimulated, antigen-specific CD8 + T cells was beyond the scope of the present study, intriguing unconventional molecular mechanisms have been uncovered that may explain how CD8 + T cells respond to extracellular antigens. 42 APC such as dendritic cells are capable of cross-presentation by transferring exogenous proteins into the MHC class I pathway 43,44 or of directly transferring antigen-laden MHC class I complexes and costimulatory molecules to expanding CD4 + T cells, which then in turn are able to present these epitopes to CD8 + T cells and initiate a productive cytotoxic T-cell response.…”
Section: Discussionmentioning
confidence: 99%
“…Help from CD4 T cells appears to be necessary at the time of initial antigenic activation of naive CD8 T cells (2,3), and CD4 T cells may also be required for longterm maintenance of memory CD8 T cells after Ag eradication (2)(3)(4). Deficient secondary CD8 T cell responses have also been reported when CD4 T cells are lacking at the time of Ag reactivation of memory CD8 T cells (5)(6)(7)(8)(9)(10), even if the CD8 T cells are generated in normal help conditions (5)(6)(7)(8)(9)(10). The nature of the help provided by CD4 T cells during priming of naive CD8 T cells and during maintenance or reactivation of memory cells is largely unknown and may differ in these three situations.…”
mentioning
confidence: 94%